Capital Regulation and Tail Risk - Perotti, Enrico Camillo (IMF Working Papers; Working Paper, 2011)
The paper studies risk mitigation associated with capital regulation, in a context where banks may choose tail risk asserts. We show that this undermines the traditional result that high capital reduces excess risk-taking driven by limited liability. Moreover, higher capital may have an unintended effect of enabling banks to take more tail risk without the fear of breaching the minimal capital ratio in non-tail risky project realizations. The results are consistent with stylized facts about pre-crisis bank behavior, and suggest implications for the optimal design of capital regulation.